2023
DOI: 10.3390/microorganisms11102379
|View full text |Cite
|
Sign up to set email alerts
|

The Signal Transduction Protein PII Controls the Levels of the Cyanobacterial Protein PipX

Antonio Llop,
Lorena Tremiño,
Raquel Cantos
et al.

Abstract: Cyanobacteria, microorganisms performing oxygenic photosynthesis, must adapt their metabolic processes to environmental challenges such as day and night changes. PipX, a unique regulatory protein from cyanobacteria, provides a mechanistic link between the signalling protein PII, a widely conserved (in bacteria and plants) transducer of carbon/nitrogen/energy richness, and the transcriptional regulator NtcA, which controls a large regulon involved in nitrogen assimilation. PipX is also involved in translational… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Since L65 is outside the TLD/KOW domain providing the contacts with NtcA, the reason for the rather drastic effect of L65Q on interactions with NtcA in the BACTH system is unclear. However, L65Q was identified as a spontaneous mutation suppressing PipX toxicity and it has recently been shown to decrease PipX levels in S. elongatus [20,54], which suggests the reduced formation of in vivo complexes between PipX L65Q and PII. Thus, interaction or functional assays indicated that the L65Q mutation did have phenotypic consequences that differed for PipX-PII and PipX-NtcA complexes.…”
Section: Interactions Involving Pipx-pii and Pipx-ntcamentioning
confidence: 99%
See 1 more Smart Citation
“…Since L65 is outside the TLD/KOW domain providing the contacts with NtcA, the reason for the rather drastic effect of L65Q on interactions with NtcA in the BACTH system is unclear. However, L65Q was identified as a spontaneous mutation suppressing PipX toxicity and it has recently been shown to decrease PipX levels in S. elongatus [20,54], which suggests the reduced formation of in vivo complexes between PipX L65Q and PII. Thus, interaction or functional assays indicated that the L65Q mutation did have phenotypic consequences that differed for PipX-PII and PipX-NtcA complexes.…”
Section: Interactions Involving Pipx-pii and Pipx-ntcamentioning
confidence: 99%
“…Because PipX mutations impairing binding to PII also impair PipX levels in S. elongatus [23,54,61], it was relevant to know whether GlnB and/or GlnK proteins can perform the same chaperon role in E. coli; in which case, the mutations affecting binding to GlnB and/or GlnK and PipX self-interaction should also impair protein levels.…”
Section: Mutations Impairing Pipx Binding To Glnk or Glnb In E Coli A...mentioning
confidence: 99%
“…Since L65 is outside the TLD/KOW domain providing the contacts with NtcA, the reason for the rather drastic effect of L65Q on interactions with NtcA in the BACTH system is unclear. However, L65Q was identified as a spontaneous mutation suppressing PipX toxicity and has been recently shown to decrease PipX levels in S. elongatus [20,55], which suggests reduced formation of in vivo complexes between PipX L65Q and PII. Thus, interaction or functional assays indicated that the L65Q mutation did have phenotypic consequences that differed for PipX-PII and PipX-NtcA complexes.…”
Section: Strainmentioning
confidence: 99%
“…Because PipX mutations impairing binding to PII also impair PipX in levels S. elongatus [24,55], it was relevant to know whether GlnB and/or GlnK proteins can perform the same chaperon role in E. coli, in which case the mutations affecting binding to GlnB and/or GlnK and PipX self-interaction should also impair protein levels.…”
Section: Mutations Impairing Pipx Binding To Glnk or Glnb In E Coli A...mentioning
confidence: 99%
“…Since PipX levels in S. elongatus are impaired by mutations decreasing binding to PII or by environmental conditions disrupting PipX-PII complexes [22,25,48], the prediction is that in the absence of PII the levels of PipX would be significantly impaired. To test this idea while seeking evidence that our NanoBiT derivatives maintain regulatory features, we next asked whether the presence of either PII or PII-LgBiT have a positive effect on the levels of PipX-SmBiT.…”
Section: Pii-lgbit and Pipx-smbit Retain Regulatory Features In S Elo...mentioning
confidence: 99%